Definition of rating of samples in technology of water-alcohol infusions by profile non-linear quality criteria - Koretska, Iryna; Kuzmin, Oleg; Zinchenko, Tetiana (My University, 2020)
Using a mathematical model to determine rational prescription compositions based on water-alcohol infusions of vegetable raw materials for restaurant technology.Використання математичної моделі для визначення раціональних рецептурних композицій на основі водно-спиртових настоїв рослинної сировини для технології ресторанної продукції.
Keywords: restaurant products; water-alcohol infusions; quality assessment; rating of samples; ресторанна продукція; водно-спиртові настої; оцінка якості; рейтинг зразків; кафедра технології ресторанної і аюрведичної продукції; кафедра вищої математики імені проф. Можара В. І.